2021
DOI: 10.1007/s11064-021-03270-9
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling Protein 2 Deficiency Enhances NLRP3 Inflammasome Activation Following Hyperglycemia-Induced Exacerbation of Cerebral Ischemia and Reperfusion Damage In Vitro and In Vivo

Abstract: Mitochondrial uncoupling protein 2 (UCP2) deficiency exacerbates brain damage following cerebral ischemia/reperfusion (I/R). The Nod-like receptor protein-3 (NLRP3) inflammasome also plays a vital role in cerebral I/R damage. However, the effect of UCP2 on NLRP3 inflammasome-mediated hyperglycemia and I/R damage is not clear. In the present study, UCP2-knockout (UCP2−/−) and wild-type (WT) mice were used to establish a model of middle cerebral artery occlusion (MCAO) and reperfusion under normo- and hyperglyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…5 ). In UCP2-knockout mice, activation of NLRP3 inflammasome is enhanced by increased ROS production, which exacerbates detrimental effects of ischaemia and reperfusion 58 .…”
Section: Discussionmentioning
confidence: 99%
“…5 ). In UCP2-knockout mice, activation of NLRP3 inflammasome is enhanced by increased ROS production, which exacerbates detrimental effects of ischaemia and reperfusion 58 .…”
Section: Discussionmentioning
confidence: 99%
“…These hypotheses are supported by fundamental science studies. 44,45 It is also reported that maternal diabetes exposure increases the risk of developing transient tachypnea of the neonate and respiratory distress syndrome at birth due to premature delivery and to the presence of a lower quality and quantity of pulmonary surfactant. 40,46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…These hypotheses are supported by fundamental science studies. 42,43 It is also reported that maternal diabetes exposure increases the risk of developing transient tachypnea of the neonate and respiratory distress syndrome at birth due to premature delivery and to the presence of a lower quality and quantity of pulmonary surfactant. 38,44,45 .…”
Section: Discussionmentioning
confidence: 99%